Oesophageal eosinophilia in children with coeliac disease. Issue 9 (12th April 2017) - Ari, Anne; Morgenstern, Sara; Chodick, Gabriel; Matar, Manar; Silbermintz, Ari; Assa, Amit; Mozer-Glassberg, Yael; Rinawi, Firas; Nachmias-Friedler, Vered; Shamir, Raanan; Zevit, Noam
Abstract : Objectives: An association between coeliac disease (CD) and eosinophilic oesophagitis (EoE)/oesophageal eosinophilia (EE) has been suggested. We sought to characterise children with CD+EE in-depth and assess the contribution of each condition to the clinical presentation and treatment response. Study design: Medical records of children with both CD+EE, or isolated EoE diagnosed between 2000 and 2014, were retrospectively reviewed and compared with patients with isolated CD or epigastric pain. Frequency of EE was calculated from endoscopy results of patients with suspected CD or epigastric pain between 2011 and 2014. Missing data were obtained via a telephone questionnaire. Setting: Single large, tertiary paediatric centre. Patients: 17 CD+EE, 46 EoE, 302 isolated CD and 247 epigastric pain. Results: The patients with CD+EE shared characteristics of both individual conditions. While age at diagnosis, family history of autoimmunity/CD and anaemia were similar to patients with CD, other characteristics such as male gender, personal/family history of atopy, peripheral eosinophilia and oesophageal white papules were more similar to patients with EoE. Combined patients (CD+EE) tended to present with CD-associated symptoms; the majority (63%) later developed typical EoE symptoms. Only a minority (21%) of combined patients had EE that resolved after a gluten-free diet; another 21% had normalisation of EE upon proton pump inhibitor treatment. The remainder required EoE-specific treatment. Conclusion: Patients with CD found to have EE share characteristics with both isolated CD and EoE. It appears that these are two coexisting entities presenting in the same patient rather than eosinophilia associated with CD, and therefore, interventions separately addressing each condition may be considered.